2019
DOI: 10.1055/s-0039-1696955
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Biomarkers in Clinical Management Guidelines: A Critical Appraisal

Abstract: In cardiovascular disease (CVD), biomarkers (i.e., “biological markers”) could have multiple roles in understanding the complexity of cardiovascular (CV) pathophysiology and to offer an integrated approach to management. Biomarkers could help in daily practice as a diagnostic tool, to monitor therapy response, to assess prognosis and as early marker of CV damage, or to stratify risk. In recent years, the role of biomarkers in CVD is even more relevant and some have recently been included in clinical management… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 119 publications
(88 reference statements)
0
47
0
1
Order By: Relevance
“…The ABC‐bleeding tool is a recently proposed assessment tool, which adds GDF‐15, Troponin T, and hemoglobin biological indicators to predict the risk of major bleeding events within 1 or 3 years . The ABC‐bleeding tool was derived in a highly selected anticoagulated clinical trial cohort, while the performance of the ABC‐bleeding tool confers limited advantage in a real‐world cohort due to older patients and the progression of risk factors . Therefore, patients at high risk should be assessed by the above high sensitivity tools owing to the prevalence of major bleeding was high.…”
Section: Discussionmentioning
confidence: 99%
“…The ABC‐bleeding tool is a recently proposed assessment tool, which adds GDF‐15, Troponin T, and hemoglobin biological indicators to predict the risk of major bleeding events within 1 or 3 years . The ABC‐bleeding tool was derived in a highly selected anticoagulated clinical trial cohort, while the performance of the ABC‐bleeding tool confers limited advantage in a real‐world cohort due to older patients and the progression of risk factors . Therefore, patients at high risk should be assessed by the above high sensitivity tools owing to the prevalence of major bleeding was high.…”
Section: Discussionmentioning
confidence: 99%
“…Thrombosis and Haemostasis predict mortality. Nevertheless, Esteve-Pastor et al 26 suggested that most biomarkers will improve on clinical risk stratification, but awaiting biomarker results may lead to delays in the initiation of therapy. Therefore, the application of biomarker-based predictive models has some limitations in clinical practice.…”
Section: Thrombosis and Haemostasismentioning
confidence: 99%
“…Nevertheless, the clinical usefulness of biomarkers when they are evaluated alone may be only limited. In fact, a common criticism of biomarkers is their high variability and lack of specificity in different clinical settings [38][39][40]. However, an advantage of miRNAs compared to other biomarkers is their plasma stability, which makes them less likely to be altered due to acute conditions [9,41], even though results from miRNAs levels should be interpreted with caution and contextualized according to clinical risk factors.…”
Section: Discussionmentioning
confidence: 99%